Breaking Barriers: The Role of 'Professional English and Communication' Courses in Medical Education - Kadagidze, Lamara (European Scientific Journal, ESJ, 2023)
The present paper explores the significant role of effective English communication in enhancing the physician-patient relationship in multicultural healthcare settings. The primary objective is to evaluate the impact of a specialized "Professional English and Communication" course on the communication skills of medical students at East-West Teaching University in Tbilisi, Georgia. Employing a mixed-methods approach, the study included a quantitative survey and qualitative feedback from a cohort of 11, both: native and non-native-speaker students of a Medical Doctor One-Cycle Educational Program. The students engaged in role-plays and discussions based on structured scenarios, which were integral components of the 13-week course. Findings indicated that the course was highly effective, with 75% of students rating it as "Very effective" in improving their professional English and communication skills. A significant percentage of students reported increased engagement and comfort in participating in class activities after the implementation of structured guidelines for role-plays. The work concludes with the affirmation of the value of targeted communication skills training in medical education, particularly through practical activities such as role-plays. Students' feedback also revealed the importance of a supportive and inclusive learning environment in promoting engagement and overcoming challenges. These findings have implications for the design of similar courses to cater to diverse student populations in the medical field. Future research should explore the long-term impact of such courses on students' professional practices and patient outcomes.